Synthesis of polyaniline with mixed nanofibre–granular morphology. (September 2013) - Abdolahi, A; Hamzah, E; Ibrahim, Z; Hashim, S
Abstract : Polyaniline (PANI) has been synthesised using a combined ultrasonic interfacial polymerisation method. Both the morphological structure and chemical compositions were analysed using field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and Fourier transmission infrared radiation (FTIR). Results from FESEM showed that a granular morphology of PANI with a partial amount of nanofibres was obtained. Results from XRD results revealed the formation of partially crystalline PANI. Analysis by FTIR also confirmed the formation of PANI. This paper aims to study synthesis of PANI with nanofibre-granular morphology.